PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, KOMPETENSI TERHADAP KINERJA PEGAWAI DINSOS KABUPATEN MAJALENGKA - Burhanudin Rabani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The Influence Of Organizational Culture Of Leadership Style And Competence On Employees Performance (A Study at Social Service of Majalengka Regency). The purpose of this study is to determine the influence of organizational culture of leadership style and competence on the performance of Social Service employees of Majalengka Regency. The method used in this research is a survey, data collection using a questionnaire then analyzed using regression analysis. The results showed that: (1) the organizational culture partially has a positive and significant influence on the performance of Service employees (sig = 0,000); (2) the leadership style partially has a negative influence and has no significant influence on the performance of Service employees (sig = 0.246); (3) competency partially has a positive and significant influence on the performance of Service employees (sig = 0,000); (4) simultaneously the organizational culture and competence have a positive and significant influence on employees performance. As for the leadership style variables has negative simultaneous and has no significant influence on the performance of Service employees. Organizational culture, leadership style and competence give an influence of 64.2% on the performance of Social Service employees (R2 = 0.642), the remaining 35.8% was influenced from other variables.